Osteoid osteoma of the mandible: A case report with review of the literature - Ankur Singh; Monica Charlotte Solomon (Elsevier, 2017)
Osteoid osteoma is a benign skeletal neoplasm most frequently observed in young individuals. The tumor most commonly occurs in the femur, the tibia, and the phalanges; however, jaw lesions are very rare. Herein, we report a rare case of osteoid osteoma that presented in the mandible of a 20-year-old boy. This report also reviews the cases of osteoid osteomas of the jaws that have been reported in the English literature so far.